DELIZIA SELF SERVICE APPLICATION USING UX DESIGN AND ANDROID STUDIO - Fernandus Felix Heriyanto; Hari Setiabudi Husni (Asosiasi Dosen Muda Indonesia, 2023)
Delizia Self Service is a tart ordering service application using the concept of Self Service Technology (SST). In this application there are 2 kinds of prospective users, in terms of customers to order tarts who can choose directly the tarts they want and even customers can also customize tarts according to their tastes. And in terms of admin which is useful for managing products, from adding products, deleting products and modifying products. Based on its function, this application provides benefits such as providing alternative means of selling tarts, increasing sales value, increasing interest, user experience, satisfaction, and comfort of buyers when ordering tarts. This journal focuses on developing application recommendations by designing the UI/UX of the Delizia Self Service Application and realizing it using Android Studio, using the System Development Life Cycle (SDLC) method with the prototype model.